I'm not too sure on how the problems should be laid out, but here goes.
I am trying to solve for M, but I can only get so far. I'm sure I saw this type of thing once in a math texbook under identity tables, it was laid out with the unsolvable equation and a simplified or reduced equivalent beside it. Anyway, I can't solve for M:
(1-A/A[sub:yntjpj62]0[/sub:yntjpj62])/(1-A/A[sub:yntjpj62]0[/sub:yntjpj62]M) => ((A[sub:yntjpj62]0[/sub:yntjpj62]-A)/A[sub:yntjpj62]0[/sub:yntjpj62])/((A[sub:yntjpj62]0[/sub:yntjpj62]M-A)/A[sub:yntjpj62]0[/sub:yntjpj62]M) => ((A[sub:yntjpj62]0[/sub:yntjpj62]-A)*M)/(A[sub:yntjpj62]0[/sub:yntjpj62]M-A) => (A[sub:yntjpj62]0[/sub:yntjpj62]M-AM)/(A[sub:yntjpj62]0[/sub:yntjpj62]M-A) =>?
Could someone please help?
Thanks in advance.
I am trying to solve for M, but I can only get so far. I'm sure I saw this type of thing once in a math texbook under identity tables, it was laid out with the unsolvable equation and a simplified or reduced equivalent beside it. Anyway, I can't solve for M:
(1-A/A[sub:yntjpj62]0[/sub:yntjpj62])/(1-A/A[sub:yntjpj62]0[/sub:yntjpj62]M) => ((A[sub:yntjpj62]0[/sub:yntjpj62]-A)/A[sub:yntjpj62]0[/sub:yntjpj62])/((A[sub:yntjpj62]0[/sub:yntjpj62]M-A)/A[sub:yntjpj62]0[/sub:yntjpj62]M) => ((A[sub:yntjpj62]0[/sub:yntjpj62]-A)*M)/(A[sub:yntjpj62]0[/sub:yntjpj62]M-A) => (A[sub:yntjpj62]0[/sub:yntjpj62]M-AM)/(A[sub:yntjpj62]0[/sub:yntjpj62]M-A) =>?
Could someone please help?
Thanks in advance.